Age-independent rise of inflammatory scores may contribute to accelerated aging in multi-morbidity - Maria Stepanova; Edgar Rodriguez; Aybike Birerdinc; Ancha Baranova (2015)
// Maria Stepanova 1, 2 , Edgar Rodriguez 1 , Aybike Birerdinc 1, 2 , Ancha Baranova 1, 2, 3, 4 1 Center for the Study of Chronic Metabolic Diseases, School of System Biology, George Mason University, Fairfax, VA, USA 2 Betty and Guy Beatty Center for Integrated Research, Inova Health Systems, Falls Church, VA, USA 3 Research Center for Medical Genetics RAMS, Moscow, Russian Federation 4 Atlas Biomed Group, Moscow, Russia Correspondence to: Ancha Baranova, e-mail: abaranov@gmu.edu Keywords: multi-morbidity, C-reactive protein, systemic inflammation, Glasgow Prognostic Score, aging Received: October 21, 2014      Accepted: November 10, 2014      Published: February 10, 2015 ABSTRACT Aging is associated with an increase in a chronic, low-grade inflammation. This phenomenon, termed “inflammaging” is also a risk factor for both morbidity and mortality in the elderly. Frequent co-occurrence of chronic diseases, known as multi-morbidity, may be explained by interconnected pathophysiology of these conditions, most of which depend on its inflammatory component. Here we present an analysis of the U.S. National Health and Nutrition Examination Survey data collected between 1999 and 2008, for the presence, and the number, of chronic diseases along with HDL-cholesterol, C-reactive protein, white blood cell count, lymphocyte percent, monocyte percent, segmented neutrophils percent, eosinophils percent, basophils percent, and glycohemoglobin levels. Importantly, even after adjustment for age and BMI, many inflammatory markers continued to be associated to multi-morbidity. C-reactive protein (CRP) levels and Glasgow Prognostic Score (GPS) were most dramatically increased in parallel with an accumulation of chronic diseases, and may be utilized as multi-morbidity predictors. These observations point at background inflammation as direct, age-independent contributor to an accumulation of the disease burden. Our findings also suggest a possibility that systemic inflammation associated with chronic diseases may explain accelerated aging phenomenon previously observed among the patients with heavy disease burden.